The smallest Cyrtoscydmini of Australia: revision of Microscydmus Saulcy & Croissandeau and Penicillidmus gen. n. (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2014)
The Australian members of Microscydmus are revised, and a new subgenus Scydmomicrus subgen. n. is established to accommodate seven species: M. (Sc.) australiensis Franz (type species of Scydmomicrus), M. (Sc.) nasicornis Franz, M. (Sc.) capitiseboraci sp. n., M. (Sc.) queenslandicus sp. n., M. (Sc.) styxianus sp. n., M. (Sc.) edithensis sp. n., and M. (Sc.) tooloomensis sp. n. A new Microscydmus-like genus, Penicillidmus gen. n., is described to include Penicillidmus masseyensis sp. n. (type species of Penicillidmus) and P. unicolor sp. n. Species of Microscydmus and Penicillidmus are distributed along the eastern coast of Australia, from the northern Cape York to northeastern New South Wales, and females of an undescribed Microscydmus are recorded from southern New South Wales. The revised taxa comprise the smallest Australian Cyrtoscydmini, with body lengths of only 0.50–0.65 mm (Microscydmus) and 0.83–0.86 mm (Penicillidmus). For comparative purposes, morphological details of the type species of Microscydmus, M. nanus, are described, and structures of the new subgenus and new genus are illustrated. Variations of character states within Microscydmus found among Australian species are discussed.